Treasure Hunt: Strengthen Collaboration Skills within the Global Diversity Dimension among Elementary School Students - Mashfufah, Aynin; Pristiani, Riska; Rufiana, Intan Sari; Hardhita, Rizki Septa; Mirayanti (Jurnal Pedagogi dan Pembelajaran, 2024)
The limitations of teaching materials and the use of inappropriate learning strategies cause students to be less than optimal in developing their skills, especially collaboration. The purpose of this research is to develop a Treasure Hunt learning strategy to strengthen collaboration skills in the dimension of Global Diversity in elementary school students. The research method used is research and development with the ADDIE model. Testing learning strategies on students' collaboration skills in the implications of Global Diversity used a one-group pretest-post-test design involving 32 fourth-grade elementary school students. This study used instruments in the form of tests and rubrics for assessing the implementation of learning. Data collection used test and observation methods. Pretest and post-test data were analyzed using nonparametric statistical tests while students' collaboration skills were analyzed descriptively quantitatively. Based on the results of testing and data analysis, there is a development of Global Diversity implications from before and after learning with the Treasure Hunt learning strategy that integrates media in the form of comics, puzzles, and videos. Students' collaboration skills can be observed during the learning process and show students can share tasks in groups or complete treasure hunts together to achieve the Global Diversity Mission. Thus, learning strategies that facilitate learners with collaborative activities indoors and outdoors can activate student cooperation to successfully achieve group goals.